The Effect of Geoboard Media Usage Toward Understanding the Geometric Concept for Student with Mild Intelectual Disability - Sielmy Dwi Kurnia; Endro Wahyuno; Sulthoni Sulthoni (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2020)
The intellectual mild on mild intelectual disability students causes students to become less in their environmental and academic response. Mild intelectual disability students have difficulty in remembering a name or form. This study aims to determine the value in the students can before and after using the media geoboard and know-how big influence of geoboard media to understanding the geometric concept. This research method used Pre-experimental One Group Pretest-posttest. The subjects of this study were students of mild intelectual disability in SLB PGRI Dlanggu Mojokerto, which amounted to 5 students. Data were collected by using written test method before treatment and after treatment with the same problem. There is a comparative value of pretest average and posttest average of 54%. So the conclusion of this research "There is a significant influence of geoboard media on the understanding of the geometric concept of students with mild intelectual disability SLB PGRI Dlanggu Mojokerto". Keywords: Geoboard Media, Flat Awakening Concept, Mild Mental Retardation